PTH-045 Endoscopic Submucosal Dissection for Early Gastric Neoplasia; Prospective Outcomes from a Single Tertiary Centre. (4th June 2013) - Haidry, R J; Butt, M; Louis-Auguste, J; Novelli, M; Lovat, L; Banks, M
Abstract : Introduction: Gastric cancer is the 4th leading cause of cancer death worldwide. Prognosis remains poor, largely due to late diagnosis. Early gastric neoplasia carries a far better prognosis with a 5 year survival of 85%. Traditionally, gastrectomy is the definitive loco-regional treatment, but carries significant perioperative morbidity. For early gastric cancer without risk of nodal metastasis, endoscopic en bloc resection with endoscopic submucosal dissection (ESD) is a feasible alternative. We present a prospective cohort analysis of patients with early gastric neoplasia undergoing ESD at a single tertiary Centre in the United Kingdom Methods: Patients were all referred through local cancer networks after staging to exclude metastatic disease. Patients underwent gastroscopy with biopsy for histology and contrast computed tomography (CT) for staging. High definition endoscopy & chromoendoscopy with indigo carmine were used to help delineate lesions. Pathology was confirmed by expert GI pathologists prior to resection. Surgery was discussed with all patients as an alternative to ESD. All gastric ESD were performed under propofol sedation by a single endosocopist with specialist training. Results: Over 24 months, 19 patients underwent ESD. Mean age was 71 years (range 23–87). 68% were male. Two lesions (10%) were in the proximal stomach, 1 in mid body (5%) 16 in distal stomach (85%). Mean resection size was 28mm (15–58). Mean resection time was 71 mins from intubation. En-bloc resection was achieved in 15/19 (74%) patients. 16/19 patients (84%) had a clear deep resection margin. Resection histology was high grade dysplasia in 52%, carcinoma in situ 11%, LGD 5%, poorly differentiated adenocarcinoma 21%, neuroendocrine tumour in 5%. 13/16 with clear resection margins post ESD remain in follow up. Of these 11/13 (87%) remain free of disease at most recent biopsy (median follow up 6 months, range 0–38). Both recurrences were LGD at the resection site. One was treated with laser ablation and the other with repeat ESD. There were no perforations or bleeding seen in our cohort during ESD Conclusion: In this small cohort of early gastric neoplasia, ESD appears to provide a safe and effective alternative to surgery with encouraging durability although our follow up time is short. Early recognition of lesions is essential to offer patients a minimally invasive curative intervention. With increasing use of high definition endoscopy more patients will become eligible for therapy. Long term durability remains to be seen. Disclosure of Interest: None Declared.